2014
DOI: 10.12944/cwe.9.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Per cent in Different Components of Tree Species and Soil Organic Carbon Pool Under these Tree Species in Kashmir Valley

Abstract: Carbon is a critical element that trees accumulate and use to support their structure and sustain physiological processes. Besides being a key element in forest ecosystems, carbon is also essential for sustaining life on a global scale. The study attempted to quantify carbon per cent in different tree components of Cedrus deodara, Fraxinus floribunda and Ulmus wallichiana,an important tree species of Kashmir valley were planted in plantation block of Faculty of Forestry at Sher-e-Kashmir University of Agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
5
5
0
Order By: Relevance
“…When considered at the species level, this study showed that the average C content of the different parts varies significantly between the foliage and the woody parts (branches and the trunk). These results are consistent with those of Wani and Qaisar (2014) , and Bayen et al. (2016) who also found a significant difference of the C content in the different parts of Deodara cedrus , Fraxinus floribunda , Ulmus wallichiana and Jatropha curcas , in the tropical zone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When considered at the species level, this study showed that the average C content of the different parts varies significantly between the foliage and the woody parts (branches and the trunk). These results are consistent with those of Wani and Qaisar (2014) , and Bayen et al. (2016) who also found a significant difference of the C content in the different parts of Deodara cedrus , Fraxinus floribunda , Ulmus wallichiana and Jatropha curcas , in the tropical zone.…”
Section: Discussionsupporting
confidence: 92%
“…When considered at the species level, this study showed that the average C content of the different parts varies significantly between the foliage and the woody parts (branches and the trunk). These results are consistent with those of Wani and Qaisar (2014), and Bayen et al…”
Section: Balanites Aegyptiaca Tagb and C Content Allotment Within Tree Across Two Climatic Zonessupporting
confidence: 92%
“…The findings also showed an increasing trend in carbon content from leaves to branches with significant variations between tree components. This corroborates several studies conducted in tropical ecosystems (Negi et al 2003;Fonseca et al 2011;Wani and Qaisar 2014;Bayen et al 2015;Dimobe et al 2018a). Our results suggest that the more biomass allocated to a given tree component, the higher the carbon will be stored in that part (Negi et al 2003).…”
Section: Distribution Of Aboveground Biomass and Carbonsupporting
confidence: 92%
“…Indeed, forests sequester and store more carbon than any other terrestrial ecosystem (Gibbs et al 2007). Thus, they represent the major terrestrial carbon sinks and pools (Gibbs et al 2007;Pan et al 2011), which play a significant role in the global carbon cycle (Fonseca et al 2011;Vashum and Jayakumar 2012;Wani and Qaisar 2014). Because sustainably managed forests can greatly contribute to mitigating climate change (Wani and Qaisar 2014;Mensah et al 2016a;Yang et al 2017), economic incentives have been devised to offset carbon inputs by reducing emissions due to deforestation and forest degradation (REDD?).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have reported carbon stocks under different tree species of Kashmir valley in India [5][6][7] . However these studies are limited to few selected species like Cedrus deodara, Fraxinus floribunda and Ulmus wallichiana.…”
mentioning
confidence: 99%